Effects of intraperitoneally-administered vitamin E and selenium on the blood biochemical and haematological parameters in rats - Çay, M; Naziroglu, M (John Wiley & Sons Ltd, 1999)
The aim of this work was to determine the role of intraperitoneally-administered vitamin E and selenium on the biochemical and haematological parameters in the blood of rats. Thirty-two adult male Wistar rats were used in this study. All rats were randomly divided into four groups. The first group was used as the control. The second group was intraperitoneally administered with vitamin E (+/-alpha-tocopheroryl acetate, 10 mg day(-1)), the third group with Se (Na2SeO3 0.2 mg over a day), and the fourth group with vitamin E and Se (vitamin E 10 mg + Na2SeO3 0.2 mg over a day). This administration was done for 5 weeks. Blood samples were taken from animals at the end of the dosage period and biochemical parameters in serum samples and haematological parameters in total blood were determined. The levels of total cholesterol (p < 0.01) and number of white blood cells (p < 0.001) in blood were significantly higher in the vitamin E group than in the control group. The levels of ALP, total cholesterol (p < 0.01) and number of white blood cells(p < 0.01) in blood were significantly higher in the selenium group than in the controls. The levels of glucose (p < 0.05), ALP (p < 0.01), total cholesterol (p < 0.001) and number of white blood cells (p < 001) were higher in the vitamin E and selenium combined group than in the controls. Other parameters considered within this trial (ALT, LDH, creatinine, albumin, total protein, amylase, creatine kinase, HDL, triglycerides, total lipid, sodium, chloride, uric acids, red blood cell, haemoglobin, packed cell volume, MCV, MCH, MCHC) did not show statistically significant differences between the control and injected groups. The results indicated that blood glucose and total cholesterol levels, ALP activity and white blood cell counts were significantly increased by intraperitoneal administration of vitamin E and selenium in rats. Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: vitamin E; selenium; biochemical values; haematological parameters; rat